Ecological peculiarities and food spectrum research of non-fish water products in Mingachavir and Varvara reservoirs in Azerbaijan - F.R. Gulieva (University of Guilan, 2021)
The present study evaluates the ecological features and food spectra of non-fish water products in Mingachevir and Varvara reservoirs in Azerbaijan. It is established that ecological peculiarities and food spectrum of long-toed river crayfish depend and change not only on the place and living conditions, but also on its age. In addition to environmental features, changes in the nutritional spectrum of long-toed river crayfish at different stages of ontogenesis have also been studied.